UJI EFEKTIFITAS ASAP CAIR CANGKANG BUAH KARET (Hevea braziliensis) SEBAGAI ANTIBAKTERI Bacillus subtilis - Lia Retno Sari; Sumpono Sumpono; Elvinawati Elvinawati (ALOTROP, 2019)
The purpose of this research was know the effectiveness quid smoke the liquid smoke of the rubber (Hevea braziliensis)  shell.The manifacture and purification of liquid smoke is carried out by 4 stages: pyrolysis, sedimentation, distillation, redestilate. The first of the research is calculating phenol levels, total acid, pH, and type weights The results showed that the feeding of rubber  (Hevea braziliensis) shell liquid Smoke proved to inhibit the growth of bacteria Bacillus subtilis where the higher the concentration of liquid smoke, the greater the resistance. The phenol levels contained in the liquid smoke of the rubber shells were obtained at 0.84% with a total acid rate of 4.725%, and a  pH at  2.548 and a density at 1.004. Antibacterial test using disc paper with see diameter clear zone. Bacterial using is pure cultur Bacillus subtiis bacteria. The concentration liquid smoke to antibacteral test is 5%, 10%, 15%, 20% and 25%. Of the five treatment obtained KHM 20% with diameter clear zone is 5,21 mm. Analysis results using One Way ANOVA obtained F hitung ? f tabel then there Significant differences Against the resulting clear zone.